Testing of tactical performance in youth elite soccer - Memmert, D. (Journal of Sports Science & Medicine, 2010)
This is a twofold study with the goals of evaluating tactical oriented game test situations for 12-13-year old highly-talented soccer players and to analyze dynamic, intra-individual developments of the players. A cross-sectional design was carried in study 1, using game test situations to measure specific tactics and creative performance for 195 expert players. The results from five evaluation criteria show that both diagnostic instruments can be used for recording football-specific creativity and game intelligence in talented young players. They produced tactical indicators that can be described as objective and valid, exhibit a sufficient degree of differentiation and are easy to record. Study 2 uses a longitudinal design to present a dynamic performance diagnostic tool for analyzing intra-individual improvements of German Soccer Foundation talents according to football-specific creativity and game intelligence. The results with respect to divergent tactical thinking clearly show that very different change processes were observed in the German Soccer Foundation players. Finally, the practical implications for the training process are discussed on the basis of both studies.